2020
DOI: 10.1136/jitc-2020-000733
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive germline expression of class I human leukocyte antigen (HLA) alleles and DRB1 heterozygosis predict the outcome of patients with non-small cell lung cancer receiving PD-1/PD-L1 immune checkpoint blockade

Abstract: BackgroundNivolumab is a human monoclonal antibody against programmed cell death receptor-1 (PD-1) able to rescue quiescent tumor infiltrating cytotoxic T lymphocytes (CTLs) restoring their ability to kill target cells expressing specific tumor antigen-derived epitope peptides bound to homologue human leukocyte antigen (HLA) molecules. Nivolumab is currently an active but expensive therapeutic agent for metastatic non-small cell lung cancer (mNSCLC), producing, in some cases, immune-related adverse events (irA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 42 publications
(38 reference statements)
0
28
0
Order By: Relevance
“…Since the start of ICI clinical trials, determining which patients will respond best to ICI has been a goal of clinicians and scientists. For example, reseachers have found that patients negative for the expression of the two most frequent HLA-A alleles a worse prognosis in NSCLC treated with ICI 28 , 29 . Others have found that commonly utilized medications like systemic antibiotics and proton-pump inhibitors can decrease the efficacy of ICIs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the start of ICI clinical trials, determining which patients will respond best to ICI has been a goal of clinicians and scientists. For example, reseachers have found that patients negative for the expression of the two most frequent HLA-A alleles a worse prognosis in NSCLC treated with ICI 28 , 29 . Others have found that commonly utilized medications like systemic antibiotics and proton-pump inhibitors can decrease the efficacy of ICIs 30 .…”
Section: Discussionmentioning
confidence: 99%
“…As shown in previous reports, class I and II HLA allele profiling have been correlated to either treatment response or survival in cancer patients receiving immune checkpoint blockade [ 27 , 28 , 29 ]. In fact, HLA complex plays a critical role in both the efficiency and modulation of the T cell-mediated immune response, performing the specific function of presenting tumor antigen-derived peptides to specific T cell receptors on effector T cells [ 26 , 27 , 28 ]. The epitope number as well as the peptide affinity for HLA molecules is haplotype specific, thus the same antigen may have different immunogenicity in individuals with different HLA profiles.…”
Section: Discussionmentioning
confidence: 79%
“…Another factor that directly influences the effect of immunotherapy are the human leukocyte antigen (HLA) alleles in tumor patients. A recent study demonstrated a predictive role of germinal class I HLA and DRB1 genotype for treatment with the PD-1 inhibitor nivolumab [ 34 ]. The results indicated a poor outcome in patients with non-small cell lung cancer who were negative for the most frequent HLA-A alleles, whereas patients expressing HLA-A*01 displayed prolonged progression-free survival and overall survival [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated a predictive role of germinal class I HLA and DRB1 genotype for treatment with the PD-1 inhibitor nivolumab [ 34 ]. The results indicated a poor outcome in patients with non-small cell lung cancer who were negative for the most frequent HLA-A alleles, whereas patients expressing HLA-A*01 displayed prolonged progression-free survival and overall survival [ 34 ]. A link between specific HLA haplotypes and the expression of immune checkpoints in HNSCC patients is conceivable [ 35 ] and should be investigated in future studies to find reliable biomarkers for effective immunotherapy and to protect patients that do not benefit from these therapies because of severe immune-related adverse events.…”
Section: Discussionmentioning
confidence: 99%